Estudio de las Características Psicométricas de la forma corta del Test de Beery con el modelo Rasach - Escurra Mayaute, Luis Miguel (1993)
Using the Rasch Model a study about the principie characteristics of the Short Fonn of Beery Visual Motor Integration Test developed by Salazar and Delgado (1985) was carried out. The test was administered to 1210 students (49,9% girls and 50,1% boys) corning from public and privates schools of Lima from 1st, 2nd and 3rd grades. The results show that the Short Fonn of the VMI constituted by 12 items, did not fit the Rasch model. However, when six items were eliminated a scale that fitted the model was constituted. Scores of the item-paramenters and the person-paramenters, as well as basic statistic analysis to evaluate the adjustment of the model, were computed. The validity of the model was cornpared according to the differente demographic characteristics, verifying the generability and stability of the scale. Additionaly the relation between the Rasch Scales and the Short Form was evaluated.